Approaches to Upgrading Strategies of Attracting Highly-Technological Companies to Preferential Zones of the Tula Region - U. A. Sharipov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The process of modernizing economy in the region needs problem-solving dealing with investment raising in order to renew manufacturing technologies, passing over to innovation products. The article underlines the necessity to identify and develop factors of investment appeal and to estimate the degree of their affect on economic indicators of the region. The region appeal for the investor depends on two components: investment appeal of the region itself (in view of completeness and adequacy of investment legislation, legal protection of the investor, regional state policy, etc.) and appeal of investment projects (in view of financial standing of the organization and its efficiency). The author studies the process of investment appeal shaping and proposes steps f or its identification. Initial variables to assess doubtful investment appeal are analyzed, as well as regional threats and microclimate in the region. Findings of the research can help estimate the link between power factors and investment appeal of territorial entities.